State-of-the-art and perspectives in the heavy mineral industry of Sri Lanka - Subasinghe, H. C. S. (Miner Econ, 2021)
Heavy minerals have become an essential commodity in modern-day technology. The objective of this study is to examine the current status of the heavy mineral industry of Sri Lanka. The present study also examines the economic viability of potential heavy mineral placer deposits, based on geochemical data. Field investigations suggested the occurrence of heavy minerals as beach-placers, and inland/raised beach deposits along the coastline of Sri Lanka. Geochemical results showed the enrichment of TiO(2), Fe(2)O(3), Al(2)O(3), and trace elements, and depletion of other major oxides such as Na(2)O, K(2)O, MnO, MgO, CaO, and P(2)O(5). Consequently, it suggests the abundance of ilmenite, leucoxene, rutile, sillimanite, garnet, and rare earth element (REE)-bearing heavy minerals in potential placer deposits. In contrast, this study illustrates the exported quantity (in the weight ratio of 35:3:1) of ilmenite, rutile, and zircon minerals during the last decade. Ilmenite is the dominant heavy mineral in Sri Lanka, and thus, its production and price volatilisations are essential to understand the current status and predict the future behaviour of the heavy mineral industry. Statistical observations suggest that the global production and unit price variations of ilmenite have increased gradually from 1950 to 2015. Besides, the forecasted variations in annual global production and unit price changes of ilmenite indicate healthy compound annual growth rates of 1.27% and 1.43%, respectively. However, Sri Lanka has less contribution (< 1%) to global ilmenite production. Consequently, the value addition of ilmenite must be highly encouraged with at least an immediate stage (e.g. synthetic rutile). The present study also highlights possible value addition stages of available heavy mineral resources (low-, intermediate-, or high-level value addition), and discusses action plans to improve the quality of the heavy mineral industry of Sri Lanka. In recommendations, imposing sustainable regulations and policies would uplift the heavy mineral industry of Sri Lanka. For example, value addition to local heavy minerals and terminating raw commodity export are highly recommended.